An effective resource management in cloud computing. (2017) - Shameem, P. Mohamed; Johnson, Nimmy; Shaji, R.S.; Arun, E.
Provision of resources must be provided such that all resources are made available to user's request in efficient manner to satisfy their needs. Resource allocation in virtualised environment should provide elasticity. When the workload increases, existing approaches cannot respond to the growing performance in an effective way. This may lead to the violation of service level agreement (SLA) which will decrease the quality of service (QoS). Existing methods cannot take an accurate decision on the allocation of resources in an optimal way and are not predictive in nature. Before any problems occur, they cannot take a precaution on resource management. Therefore, a framework is used to ensure effective resource management. This framework uses rough set algorithm in order to make an accurate decision on the allocation of resources. Variation in workloads is adapted by considering new parameters like type of application, garbage processing policy and internal application resources.